The role of Proline-Rich Homeodomain protein PRH/HHEX in cholangiocarcinoma - Ghouth, Nahlah (2024)
Cholangiocarcinoma (CCA) is a malignancy of the bile ducts that arises from their lining epithelial cells. CCA has increasing incidence and mortality. Proline Rich Homeodomain / Haematopoietically Expressed Homeobox Protein (PRH/HHEX) is a transcription factor that acts as an oncoprotein in CCA. Here, using cumulative growth and EdU incorporation assays, I show that PRH expression in immortalised cholangiocytes (AKN1 cells) increased cell growth and proliferation. Additionally, I show using immunofluorescence imaging and Western blotting that PRH expression in AKN1 cells induces cellular phenotypes that resembles partial epithelial to mesenchymal transition (EMT), and that this morphological transformation is accompanied by an increase in cell migration and cell invasion. Recently, PRH expression has been reported to upregulate the expression of the mesenchymal marker protein Vimentin in CCA cells. To date most published research has focused on Vimentin expression in mesenchymal cells and its roles in the cytoplasm. Vimentin is known to participate in several biological processes such as cell proliferation, EMT, cell adhesion, cell migration, and cell invasion which have been reported to be upregulated in cancer cells with the consequence of increased tumour growth and disease progress. Knowledge on the role or roles of Vimentin in the nucleus is limited. However, nuclear Vimentin was reported to exhibit gene regulatory activity in Neuroblastoma cells. To expand knowledge on the importance of Vimentin in CCA, I used a combination of high and super-resolution imaging techniques to show that PRH may spatially exist near Vimentin in the nuclear subcellular regions of CCA cells. In addition, I used siRNA to deplete Vimentin in CCA cells and to reveal that Vimentin loss inhibits cell proliferation, induces an epithelial-like morphology, and reduces cell migration. Gene ontology (GO) and Gene Set Enrichment Analysis (GSEA) of RNAseq data generated using these cells revealed that Vimentin, in conjunction with PRH, regulates multiple signalling pathways in line with the phenotype of Vimentin-depleted cells. This project provides new insights into the importance of PRH and Vimentin in CCA. The novel PRH and Vimentin spatial organisation and the identified target genes co-regulated by PRH and Vimentin serve as new potential targets for future interventional studies.